Baseline and longitudinal change in blood pressure and mortality in a Chinese cohort. Issue 12 (4th August 2018) - Wang, Jian-Bing; Huang, Qiu-Chi; Hu, Shu-Chang; Zheng, Pei-Wen; Shen, Peng; Li, Die; Lu, Huai-Chu; Gao, Xiang; Lin, Hong-Bo; Chen, Kun
Abstract : Background: A J-curve association has been demonstrated for blood pressure (BP) and all-cause mortality, but data on longitudinal change of BP and mortality in Chinese population are limited. Methods: We performed a retrospective cohort study to examine the association between BP (at baseline and longitudinal change) and risk of mortality in Yinzhou District, Ningbo, China, based on the Yinzhou Health Information System. At baseline, a total of 181 352 subjects aged over 18 years with at least one BP examination record were recruited through the Yinzhou Health Information System. The final analysis was restricted to 168 061 participants after exclusion of outliers of BP. Results: A U-shaped association was observed for BP at baseline and risk of total and cardiovascular mortality. When compared with normotensive participants, patients with hypotension (HRs=1.51, 95% CI 1.21 to 1.88) and stage 3 hypertension (1.28, 95% CI 1.09 to 1.50) had an increased risk of all-cause mortality. Relative to stable BP of normotension, having a rise in BP from normotension to hypertension or from prehypertension to hypertension both conferred an increased risk of total and cardiovascular mortality (total: 1.39 (95% 1.10 to 1.75) and 1.40 (95% 1.15 to 1.69); cardiovascular: 2.22 (95% CI 1.35 to 3.65) and 1.89 (95% CI 1.20 to 2.96), respectively). Conclusions: Our findings emphasise that hypotension and stage 3 hypertension were associated with an increased risk of all-cause mortality. Longitudinal change from normotensive or prehypertensive levels to 140/90 mm Hg or higher could increase the risk of total and cardiovascular mortality.